Effects of dezocine and ropivacaine infiltration anesthesia on cellular immune function indicators, anesthesia recovery time and pain factors in patients with open liver resection - Zhu, Ronggang; Du, Tingting; Gao, Hongzhu (Cellular and Molecular Biology, 2020)
The current experiment was carried out to explore the effects of dezocine combined with ropivacaine infiltration anesthesia on the anesthesia recovery time and pain factors of patients with open hepatectomy. A prospective randomized controlled method was used to select 92 patients with open liver cancer resection in our hospital from August 2017 to November 2019. The patients were divided into a study group (n=46) and a control group (n=46) using a computer-generated random number table. Both groups underwent general anesthesia, based on this, the study group was treated with ropivacaine infiltration anesthesia 10 minutes before skin incision, and dezocine was given intravenously 0.5 h before surgery, the control group was anesthetized with ropivacaine 10 minutes before the incision, and was given a saline injection 0.5 h before the operation. Compared the recovery of anesthesia (recovery time of spontaneous breathing, time to open eyes, time to extubation), the incidence of adverse reactions, and cellular immune function indicators (peripheral blood CD4+, CD4+/CD8+, NK cell levels), stress response indicators [serum blood glucose (Glu), norepinephrine (NE), adrenaline (E)], pain factors [serum dopamine (DA), neuropeptide Y (NPY), substance P (SP)] before induction of anesthesia (T0), completion of surgery (T1), 12 hours after surgery (T2), and 24 hours after surgery (T3) between the two groups, and the degree of pain (VAS score) at T2 and T3 were compared between the two groups. The levels of CD4+, CD4+/CD8+, and NK cells in peripheral blood at T1, T2, and T3 in the study group were higher than those in the control group (P<0.05); serum Glu, NE, and E levels in the study group at T1, T2, and T3 were lower than those in the control group (P<0.05); serum DA, NPY, and SP levels in the study group at T1, T2, and T3 were lower than those in the control group (P<0.05); the VAS scores of the study group at T2 and T3 were lower than those of the control group (P<0.05); the time of spontaneous breathing recovery, eyes opening and extubation in the study group were shorter than those in the control group (P<0.05); the incidence of restlessness (4.35%), transient hypertension (6.52%), and cough (2.17%) in the study group were lower than those in the control group (P<0.05). Dezocine and ropivacaine infiltration anesthesia can significantly shorten the recovery time of anesthesia and inhibit pain factor secretion in patients with open hepatectomy and can reduce the body’s stress response after surgery, reduce immune function fluctuations, and can reduce the incidence of adverse reactions to anesthesia, and help promote patients’ postoperative recovery.